2018
DOI: 10.1016/j.athoracsur.2017.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy Versus Surgery for Early Lung Cancer Among US Veterans

Abstract: Among a large cohort of early stage lung cancer patients, we found that lobectomy had improved survival compared with SBRT, although we found no survival difference between sublobar resection and SBRT. Despite these findings, the potential for unmeasured confounding remains and prospective randomized trials are needed to better compare these treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 30 publications
1
50
0
2
Order By: Relevance
“…3 At the same time, nonsurgical modalities, such as stereotactic body radiotherapy (SBRT), are increasingly being offered to patients with these small lesions, which may address the primary tumor but not the lymph nodes. 4 Previous prospective and retrospective studies of early-stage disease have varied in methodology and most often included patients with larger tumors up to 3 cm in diameter, reflecting prior classifications of what constitutes stage IA NSCLC. [5][6][7][8][9][10][11][12][13][14][15] Understanding the location in addition to the incidence of occult nodal metastases is crucial if we are to diverge from the traditional gold standard of lobectomy with complete lymphadenectomy.…”
mentioning
confidence: 99%
“…3 At the same time, nonsurgical modalities, such as stereotactic body radiotherapy (SBRT), are increasingly being offered to patients with these small lesions, which may address the primary tumor but not the lymph nodes. 4 Previous prospective and retrospective studies of early-stage disease have varied in methodology and most often included patients with larger tumors up to 3 cm in diameter, reflecting prior classifications of what constitutes stage IA NSCLC. [5][6][7][8][9][10][11][12][13][14][15] Understanding the location in addition to the incidence of occult nodal metastases is crucial if we are to diverge from the traditional gold standard of lobectomy with complete lymphadenectomy.…”
mentioning
confidence: 99%
“…Although a systematic review of studies using propensity score analyses reported better overall survival comparing sublobar resection with SBRT and no difference in lung cancer-specific survival, 12 a large analysis among US veterans reported no difference in cancer-specific survival, noncancer survival, and overall survival between patients treated with sublobar resection (n ¼ 634) and patients treated with SBRT (n ¼ 449). 23 In the near future, results from several randomized trials comparing sublobar resection with lobectomy will be reported.…”
Section: Bryan M Burt Mdmentioning
confidence: 99%
“…The multivariable analysis considering long‐term survival found higher cancer‐specific mortality associated with SABR compared with lobectomy (hazard ratio 1.45, 95% CI: 1.09–1.94, P = 0.01). The mean age of this cohort was also under 75 years …”
Section: Discussionmentioning
confidence: 96%
“…The mean age of this cohort was also under 75 years. 45 Unlike current studies involving only T1 tumors, previously terminated randomized trials (the STARS trial [NCT00840749] and the ACOSOG Z4099 trial [NCT01336894]) and the presently recruiting randomized trials (the SABRTooth trial [NCT02629458] the VALOR trial [NCT02984761]) included both T1 and T2 (AJCC eighth) tumors to compare the outcomes of surgical resection and SABR. When SABR is delivered with the planning target volume receiving BED more than 100 Gy, good local control is achieved in not only T1 but also T2 tumors.…”
Section: Discussionmentioning
confidence: 99%